ANALISIS JENIS-JENIS PIGMEN ALGA COKLAT Padina australis Hauck DARI PERAIRAN LAUT SULAWESI - Kalalo, Julia L.; Mantiri, Desy; Rimper, Joice (JURNAL PESISIR DAN LAUT TROPIS, 2014)
Padina australis Hauck is one of the brown algae that belongs to a class Phaeophyceae, Dictyotales order. This species is very important because it is useful as animal feed, fertilizer, pharmaceutical ingredients, human food and cosmetics. Sample taken in marine waters Sulawesi, precisely in the waters of cape Kalasey, Tongkaina waters, and the waters Blongko. The purpose of this study is to analyze the type of pigment chlorophyll with qualitatively and quantitatively. Process of extraction is done with organic solvent, and the developer with PE and acetone (80:20). Extraction results then analyzed with a spectrophotometer at a wavelength of 380-700nm, for the type of pigment chlorophyll. Type of pigment found in the pigment extraction P. australis Hauck of three waters is chlorophyll-a and chlorophyll-b, with an average concentration of chlorophyll-a value that is the highest in the waters Blongko 0.381 µg/ml in PTK3, with a range from 0.293 to 0.381 µg/ml, and lowest in the waters Tongkaina is 0.143 µg/ml PT3, with a range from 0.431 to 0.30 µg/ml.